2005
DOI: 10.1103/physreve.71.021304
|View full text |Cite
|
Sign up to set email alerts
|

Ejection of dust by elastic waves in collisions between millimeter- and centimeter-sized dust aggregates at16.5to37.5msimpact velocities

Abstract: We report on experiments in which millimeter-sized Si O2 dust aggregates consisting of (sub)-micrometer-sized grains impact into centimeter-sized targets that consist of the same kind of dust particles. The porosity of the granular targets is between 74% and 88%. Impact speeds are between 16.5 and 37.5 m/s with most impacts around 25 m/s . Compaction of the target by the impacting dust aggregate creates a crater which is several millimeters deep and 2-3 cm in diameter. We do not detect a significant amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
3
22
0
3
Order By: Relevance
“…which agrees with non-zero-gravity experiments of Wurm et al (2005a), who estimated a mass loss of 10 projectile masses for velocities of more than 1650 cm s −1 . Due to the small variation in projectile mass within each of the two experiments, we apply a power-law in mass and merge both experiments to …”
Section: F2: Erosionsupporting
confidence: 80%
See 1 more Smart Citation
“…which agrees with non-zero-gravity experiments of Wurm et al (2005a), who estimated a mass loss of 10 projectile masses for velocities of more than 1650 cm s −1 . Due to the small variation in projectile mass within each of the two experiments, we apply a power-law in mass and merge both experiments to …”
Section: F2: Erosionsupporting
confidence: 80%
“…) found that the target aggregate is efficiently eroded (F2) if the impact velocities exceed 1500 cm s −1 . This mass loss of the target was also observed in the case of larger projectiles into porous targets (Wurm et al 2005a;Paraskov et al 2007). Similar to the F1 fragmentation, it may occur that one aggregate is porous while the other one is compact.…”
Section: Classification Of the Laboratory Experimentsmentioning
confidence: 61%
“…In experiments with velocities larger than 9 m/s and using compact dust aggregates with a volume filling of ∼33%, sticking is observed together with fragmentation (Wurm et al 2005b;Teiser & Wurm 2009). In similar collision experiments at comparable velocities but with a porous target only fragmentation was observed (Wurm et al 2005a). Due to the fragmentation, sticking and bouncing it is not clear how such a body evolves further.…”
Section: Introductionmentioning
confidence: 84%
“…If further growth is possible depends on the properties of the decimetre-size dust aggregates. Wurm et al (2005a) found that highly porous (granular) dust aggregates are destroyed by impacts of sub-cm bodies at large impact velocities. In contrast, Teiser & Wurm (2009) and Wurm et al (2005b) showed that growth up to ∼60 m/s is possible if the target is compact (33% filling factor).…”
Section: Introductionmentioning
confidence: 99%
“…The drift can move meter-sized particles all the way in within only 100 orbits (Weidenschilling 1977). Relative velocities of large bodies set another barrier against the accumulation of large particles (Weidenschilling & Cuzzi 1993;Wurm et al 2005a;Ormel & Cuzzi 2007). A recent study by Johansen et al (2006b) shows, however, that planetesimals might be produced by a gravitational collapse in the presence of turbulence.…”
Section: Introductionmentioning
confidence: 99%